Evaluation of ELISA kits for brucellosis in naturally infected Indian cattle population by latent class analysis - TRANGADIA, B J; TOFT, N; NAGAMANI, K; RANA, S K; SRINIVASAN, V A (The Indian Journal of Animal Sciences, 2015)
Brucellosis is endemic in India and the disease is confirmed by various laboratory tests. Among the tests available, ELISA offers several advantages such as ease, cost effectiveness and possibilities of automation for screening large number of serum samples at any given period of time. This study was performed to evaluate 5 commercially available indirect ELISA kits and 1 competitive ELISA kit in naturally infected cattle population in India. Six organized cattle herds located in Andhra Pradesh, Gujarat and Odisha were selected. Sensitivity (Se) and specificity (Sp) of the tests were estimated in absence of gold standard using latent class analysis. Nearly perfect Sp was achieved by the CEDI test 99.8% (95%; credibility posterior interval (CPI) = 98.9-100%), Chekit test 99.4% (95%; CPI = 98.3-99.9%) and Svanova test 99.2% (95%; CPI = 99.2-99.9%). Se of the 5 indirect ELISA was ranged between 75.0 and 77.3%. However, a Se of 56.1% (95%; CPI= 36.1-75.1%) and Sp of 91.7% (95%; CPI = 88.7- 94.2%) were recorded for cELISA.